al-Wasâil al-Ta’lîmiyah fî Ta’lîm Mahârah al-Istimâ’ - Muhammad Rifqi Halim (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2020)
Media in a learning is among the very important elements in addition to other learning elements such as material, methods and objectives. Media has an important role in realizing learning objectives, with the use of learning media can be efficient and effective. In this paper, the researcher tries to explain about learning media specifically that can be applied in teaching listening skills. Many of the learning media can be used to carry out and streamline learning in listening skills. This type of research is included in qualitative descriptive research or literature research, the research data is the result of studies or information from books and other written works. The learning media that can be applied in teaching listening skills are video media, loudspeakers (with cable and cellular), radio, CD-ROM, acting, face-to-face conversation, educational TV, audio cassettes and language labs.